f(

g(1) -> g(0)

R

↳Dependency Pair Analysis

F(X, g(X)) -> F(1, g(X))

G(1) -> G(0)

Furthermore,

R

↳DPs

→DP Problem 1

↳Instantiation Transformation

**F( X, g(X)) -> F(1, g(X))**

f(X, g(X)) -> f(1, g(X))

g(1) -> g(0)

On this DP problem, an Instantiation SCC transformation can be performed.

As a result of transforming the rule

one new Dependency Pair is created:

F(X, g(X)) -> F(1, g(X))

F(1, g(1)) -> F(1, g(1))

The transformation is resulting in one new DP problem:

R

↳DPs

→DP Problem 1

↳Inst

→DP Problem 2

↳Remaining Obligation(s)

The following remains to be proven:

**F(1, g(1)) -> F(1, g(1))**

f(X, g(X)) -> f(1, g(X))

g(1) -> g(0)

Duration:

0:00 minutes